2020
DOI: 10.26468/trakyasobed.679581
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation on Pre-Service Teacher’s Information and Communications Technology Competency and Computational Thinking Skills in Terms of Different Variables

Abstract: system and by taking its place among 21 st century skills, took its place amidst competencies that both teachers and students should have. Especially teachers, who are the basic factor of the education system, should have these skills because these are very important in terms of the efficiency and effectiveness of the education. Based on this statement, it was tried to determine information and communications technology competency and computational thinking skills of pre-service teachers, who is going to build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
5
0
2
Order By: Relevance
“…In this context, it can be stated that gender does not have any effect on digital literacy self-efficacy and ICT competency, and it can be stated that social studies teacher candidates of both genders use technological equipment equally. Similarly, it was concluded that there was no statistically significant difference between individuals' ICTs competencies in terms of gender in the studies conducted by Akgün (2020), Aydoğmuş and Karadağ (2020) and Şad and Nalçacı (2015) as well. Also, no statistically significant difference was found in the overall scale and the sub-factors with the exception of the Application Usage factor in the study conducted by Ocak and Karakuş (2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this context, it can be stated that gender does not have any effect on digital literacy self-efficacy and ICT competency, and it can be stated that social studies teacher candidates of both genders use technological equipment equally. Similarly, it was concluded that there was no statistically significant difference between individuals' ICTs competencies in terms of gender in the studies conducted by Akgün (2020), Aydoğmuş and Karadağ (2020) and Şad and Nalçacı (2015) as well. Also, no statistically significant difference was found in the overall scale and the sub-factors with the exception of the Application Usage factor in the study conducted by Ocak and Karakuş (2019).…”
Section: Discussionmentioning
confidence: 94%
“…There exist several studies on the information and communication technology competencies of pre-service teachers (Akgün, 2020;Aydın & Erol, 2021;Aydoğmuş & Karadağ 2020;Eryılmaz, 2018;Keleş, 2014;Şad & Nalçacı, 2015) and digital literacy self-efficacy (Ocak & Karakuş, 2019) in the related literature. However, there is no study aiming to examine the relationship between ICTs competency and digital literacy self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Hatta günümüzde eğitim alanında kullanımı bir zorunluluk halini almıştır. 21.yy'ın eğitim sistemi becerileri arasında yer alan BİT yeterlilikleri bireylerin sahip olması gereken beceriler içerisinde yer almaktadır (Akgün, 2020;Gürkan, 2023;Güven & Etçi, 2022) (Eryılmaz, 2018;Şenel & Seferoğlu, 2010).…”
Section: Introductionunclassified
“…Alanyazında öğretmenlere yönelik çalışmalar bulunmaktadır (Bişirici & Gülbahar;2023;Çelikkaya & Köşker, 2023). Öğretmen adaylarına ve farklı fakültelerde öğrenim gören öğrencilere yönelik BİT tutum ve yeterliliklerinin ayrı ayrı olarak ele alındığı görülmektedir (Akgün, 2020;Alp, 2019;Eryılmaz, 2018;Gül & Karataş, 2020;Garcia-Martinez ve diğerleri, 2020;Gündoğdu ve diğerleri, 2018;Güneş vd., 2017;Güven & Etçi, 2022;Lateef, 2020;Özarslan ve diğerleri, 2013;Slechtova, 2015;Şahin vd., 2020;Tütüncü & İleri, 2021). Bununla birlikte ön lisans öğrencilerine yönelik çalışmalara da rastlamak mümkündür (Bahar & Kaya, 2013;Başat ve diğerleri, 2020).…”
Section: Introductionunclassified
“…Likewise, while there are many studies in the literature on the use of technology in instruction, both in the preschool branch and in different branches (Akbaba & Ertaş Kılıç, 2022;Ardıç, 2021;Ardies et al, 2015;Chen & Hwang, 2019;Çetin et al, 2012;Dwivedi et al, 2019;Goh & Sandars, 2020;Gülen, 2021;Gündüzalp & Yıldız, 2020;Katrancı & Uygun, 2013;Kenar &Balcı, 2013;Köroğlu, 2014;Li et al, Miliazim Memet & Şentürk, 2021;Pazilah et al, 2019;Sarı & Kartal, 2018;Yılmaz et al, 2015;Yılmaz et al, 2016), no study has been found on the relationship between the CT skill and the attitude towards the use of technology of the preschool teachers or any other branches. In Turkish sources, only one study with pre-service teachers has been found (Akgün, 2020). Thanks to the rapid technological advances in recent years, computational thinking and concepts related to technology have become one of the basics of education such as literacy and mathematics.…”
Section: Introductionmentioning
confidence: 99%